The Use of Effective Development Communication Programmes in Abolishing Female Genital Mutilation (FGM) in Southeast Nigeria - Mercy Ifeyinwa Obichili; Adaora Nancy Emehel; Daniel Toochukwu Ezegwu (CV. Rayyan Dwi Bharata, 2023)
This study examined the use of effective development communication programmes in abolishing the practice of female genital mutilation, (FGM) in south east Nigeria. The study aimed to examine the development communication programmes employed specially for combating and abolishing FGM in southeast Nigeria; to determine the extent to which these development communication programmes helped in combating and abolishing FGM in southeast Nigeria; and to identify the challenges associated with the use of development communication programmes in combating and abolishing FGM in southeast Nigeria. The descriptive survey method was used. Findings revealed that in as much as the practice of FGM has been on a visible decline over the years, development communication programme only existed in theory and never got to the grass root. It also found out that there was no awareness of and participation in the entire intervention programme. This study recommended that focus should be given to establishing increased awareness of intervention programme, which will only commence after there is a change in the perception of the practice of female genital mutilation (FGM), and ultimately lead to the achievement of the SDG by 2030.